Comparison of the safety and efficacy between the prone split‐leg and Galdakao‐modified supine Valdivia positions during endoscopic combined intrarenal surgery: A multi‐institutional analysis. (3rd August 2021) - Hamamoto, Shuzo; Okada, Shinsuke; Inoue, Takaaki; Taguchi, Kazumi; Kawase, Kengo; Okada, Tomoki; Chaya, Ryosuke; Hattori, Tatsuya; Okada, Atsushi; Matsuda, Tadashi; Yasui, Takahiro
Abstract : Objectives: To evaluate the safety and efficacy of the prone split‐leg and the Galdakao‐modified supine Valdivia positions during endoscopic combined intrarenal surgery. Methods: A multi‐institutional, retrospective cohort study was conducted between January 2014 and December 2018. The stone‐free and complication rates were compared between the prone split‐leg and the Galdakao‐modified supine Valdivia positions. Anatomical variations were evaluated using contrast‐enhanced computed tomography imaging. Results: In total, 118 and 100 patients underwent endoscopic combined intrarenal surgery in the prone split‐leg and Galdakao‐modified supine Valdivia positions, respectively. Renal punctures in the prone split‐leg position were predominantly executed through the lower calyces (78.0%), whereas those in the Galdakao‐modified supine Valdivia position were primarily performed through the middle calyces (64.0%; P  < 0.001). Surgical duration in the prone split‐leg position was significantly shorter than that in the Galdakao‐modified supine Valdivia position (106.5 vs 126.0 min; P  = 0.0459). There were no significant differences in the stone‐free rate between the two positions (78.8% vs 76.0%; P  = 0.629). Incidences of urinary tract injury ( P  = 0.033) and febrile urinary tract infection (23.7% vs 10.0%; P  = 0.011) in the prone split‐leg position were significantly higher than that in the Galdakao‐modified supine Valdivia position. The tilt of the major renal axis was significantly greater in the prone position than the corresponding values in the oblique position (19.4° vs 8.5°; P  = 0.019). Conclusions: Anatomical variation might result in the differences of renal puncture calyx. Endoscopic combined intrarenal surgery in the Galdakao‐modified supine Valdivia position may bring equal stone‐free status, with a longer surgical time but fewer complications including febrile urinary tract infection and urinary tract injury than the prone split‐leg position.